Toxic Leadership in the Hotel Sector: Identifying Causes, Consequences and Corrective Measures ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2026)
Background: The problem of toxic leadership became a major organizational problem in the hospitality industry, and  its negative impact on the welfare of the personnel, the quality of the provided service, as well as the sustainability of  the organization. Objective: The aim of the research was to study the antecedents, consequences, and corrective factors  related to toxic leadership within the hotel sector, in the context of the Delhi-NCR area. Methodology: The quantitative  research design was used with cross-sectional design, and the data were gathered among 400 employees in 30 hotels  (3-star to 5-star group). Toxic leadership, emotional exhaustion, turnover intention, perceived service quality, and the  servant leadership were measured using structured questionnaires with validated scales. Results: The results showed  that the most common toxic leadership traits that were perceived by the hotel employees were narcissism, self-promotion,  and authoritarianism. Servant leadership was shown to be a major preventive element, and it minimized burnout and  increased job satisfaction and retention intentions. The findings indicated that organizational culture and ineffective  accountability systems promoted the presence of toxic leadership in hotels. Conclusion: This study added value to the  existing bodies of literature since it brought the toxic triangle and Job Demands- Resources models to the hospitality  environment. Pragmatic implications included leadership reforms, moral training, and start-up of anonymous feedback  to reduce the toxic effects of leadership.
Keywords: Toxic leadership, employee burnout, turnover intention, servant leadership, organizational behavior, leadership styles